DETERMINAN TRANSFER PRICING PADA PERUSAHAAN MANUFAKTUR DI BEI TAHUN 2016-2018 - Animah Animah; Ni Luh Made Deswinta Wirmadewi; Isnawati Isnawati (Jurnal Ilmiah Akuntansi Indonesia, 2021)
Transfer pricing is the policy of a company in determining the price of a transaction between parties that have a special relationship. The purpose of this study is to determine the effect of Effective Tax Rate (ETR), tunneling incentives, bonus mechanisms and foreign ownership on transfer pricing. The dependent variable in this study is transfer pricing, which is calculated by a dichotomous approach, namely by looking at the sales position of those who have related parties. The independent variables in this study are Effective Tax Rate (ETR), tunneling incentives, bonus mechanisms and foreign ownership. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the periodof 2016-2018. The sample was chosen based on the purposive sampling method, which resulted in a sample of 90 data coming from 30 companies. The results of logistic regression analysis in this study indicated that tunneling incentives affect transfer pricing, whereas Effective Tax Rate (ETR), bonus mechanism and foreign ownership have no effect on transfer pricing.